Solomon Islands - Agriculture and Rural Development Strategy : Building Local Foundations for Rural Development - World Bank (Washington, DC, 2012)
In May 2006, the Government of the Solomon Islands placed rural development at the top of its policy agenda. The Solomon Islands Government's May 2006 Policy Framework Document places emphasis on development through a bottom-up and holistic approach that encompasses the empowerment of the people through rural advancement strategies, the pursuit of the Millennium Development Goals, the revitalization of the economy, improved law and order, effective service delivery and the devolution of powers and functions and decision-making authority to the periphery. This document comprises 4 sections: Chapter I presents a review of the current rural development situation. Chapter II discusses growth prospects and opportunities in the short to medium term (2011 horizon) and medium to long term (2020 horizon). Chapter III presents the Agriculture and Rural Development Strategy (ARDS) recommendations as regards priority interventions in agriculture and rural development over the short, medium and long term. Chapter IV discusses ARDS implementation, including tailoring the approach to the different provinces, monitoring ARDS implementation, and matching resources with priorities.